Interest Rate Bands of Inaction and Play-Hysteresis in Domestic Investment - Evidence for the Euro Area - Ansgar Belke; Coletta Frenzel Baudisch; Matthias Göcke (Global Labor Organization (GLO), 2019)
The interest rate represents an important monetary policy tool to steer investment in order to reach price stability. Therefore, implications of the exact form and magnitude of the interest rate-investment nexus for the European Central Bank's effectiveness in a low interest rate environment gain center stage. We first present a theoretical framework of the hysteretic impact of changes in the interest rate on macroeconomic investment under certainty and under uncertainty to investigate whether uncertainty over future interest rates in the Euro area hampers monetary policy transmission. In this non-linear model, strong reactions in investment activity occur as soon as changes of the interest rate exceed a zone of inaction, that we call 'play' area. Second, we apply an algorithm describing path-dependent play-hysteresis to estimate investment hysteresis using data on domestic investment and interest rates on corporate loans for 5 countries of the Euro area in the period ranging from 2001Q1 to 2018Q1. We find hysteretic effects of interest rate changes on investment in most countries. However, their shape and magnitude differ widely across countries which poses a challenge for a unified monetary policy. By introducing uncertainty into the regressions, the results do not change much which may be due to the interest rate implicitly incorporating uncertainty effects in investment decisions, e.g. by risk premia.
Keywords: C32; E44; E49; E52; F21; 330; European Central Bank; interest rate; investment; monetary policy; non-ideal relay; path-dependence; play-hysteresis; uncertainty